2018
DOI: 10.1016/j.jid.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hair Follicle Morphogenesis and Hair Follicle Dystrophy in a Lipoatrophy Mouse Model of Pparg Total Deletion

Abstract: PPARγ regulates multiple aspects of skin physiology, including sebocyte differentiation, keratinocyte proliferation, epithelial stem cell survival, adipocyte biology, and inflammatory skin responses. However, the effects of its global deletion, namely of nonredundant key functions of PPARγ signaling in mammalian skin, are yet unknown because of embryonic lethality. Here, we describe the skin and hair phenotype of a whole-body PPARγ-null mouse (Pparg), obtained by preserving PPARγ expression in the placenta. Pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 63 publications
2
58
0
Order By: Relevance
“…Diabetics treated with PPARγ ligands exhibit increased sebum secretion, and these same compounds increase lipid production and sensitivity to testosterone in SZ95 and SEB‐1 sebocytes . Loss of PPARγ in mice results in SG atrophy, loss of sebum and scarring alopecia …”
Section: Factors Controlling Sebaceous Gland Homeostasismentioning
confidence: 99%
“…Diabetics treated with PPARγ ligands exhibit increased sebum secretion, and these same compounds increase lipid production and sensitivity to testosterone in SZ95 and SEB‐1 sebocytes . Loss of PPARγ in mice results in SG atrophy, loss of sebum and scarring alopecia …”
Section: Factors Controlling Sebaceous Gland Homeostasismentioning
confidence: 99%
“…Since all PPARs are widely expressed in human skin and its appendages, there is increasing interest in their role in maintaining cutaneous homeostasis and in dermatological disorders . PPAR‐mediated signalling has attracted special interest in psoriasis, atopic dermatitis, acne, skin ageing, scleroderma, melasma, lipodystrophy and skin cancer . In the context of this Focus Theme Issue , this development encourages one to also take a closer look at why and how exactly PPARs are of special interest in a translational hair research context, with a strict focus on their best‐investigated isoform, PPAR‐γ.…”
Section: Ppars In Human Biology and Skinmentioning
confidence: 99%
“…Strikingly, Karnik et al also showed that PPAR‐γ signalling is crucial for HFeSC survival in mice by demonstrating that the keratin 15 (K15) promoter‐targeted deletion of this receptor in these stem cells leads to a scarring alopecia‐like loss of HFs . Constitutive, generalized knockout of PPAR‐γ in mice also induces perifollicular inflammatory cell infiltrates and atrophy of the PSU, resulting in a scarring alopecia‐like phenotype . With this seminal work, PPAR‐γ came onto the radar of translational hair research, even though a later, laser capture microdissection‐based gene expression analysis found no significant difference in PPAR‐γ expression between lesional and non‐lesional bulge epithelium of the same LPP patient .…”
Section: The Importance Of Ppar‐γ For the Bulge Stem Cells And Its Rementioning
confidence: 99%
See 1 more Smart Citation
“…Hair follicles develop at the interaction sites between embryonic epidermis and papillary fibroblast progenitor cells. (b) During E17.5 to E18.5, development of hair follicles and dWAT are coupled 4,41,44,45,110 . Enlarged hair follicles activate several pro-adipogenic signalling pathways, including Hedgehog 45 and Bmp 48 .…”
Section: Figurementioning
confidence: 99%